Present and Future: Pharmacologic Treatment of Obesity - Mariela Glandt; Itamar Raz (Journal of Obesity)
Obesity now presents one of the biggest health problems of our times. Diet and exercise are best for both prevention and treatment; unfortunately, both require much discipline and are difficult to maintain. Medications offer a possible adjunct, but their effect is modest, they are limited by side effects, and the weight loss lasts only as long as the drug is being taken, since as soon as treatment is stopped, the weight is regained. Sibutramine, a sympathomimetic medication which was available for long-term treatment, is the most recent of the drugs to be withdrawn from the market due to side effects; in this case it was an increased risk of cardiovascular events. This paper reviews those medications which are available for treatment of obesity, including many of those recently taken off the market. It also discusses some of the newer treatments that are currently being investigated.